1993
DOI: 10.1007/bf00685670
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged retention of high concentrations of 5-fluorouracil in human and murine tumors as compared with plasma

Abstract: Concentrations of 5-fluorouracil (5-FU) and its active metabolite 5-fluoro-2'-deoxy-5'-monophosphate (FdUMP) were measured in biopsy specimens of tumor tissue, normal mucosa, metastatic liver nodules, and normal liver tissue obtained from 39 patients and in two murine colon tumors (colon 26 and colon 38) after a single injection of 5FU at a therapeutic dose (500 mg/m2 and 100 mg/kg, respectively). These data were compared with plasma concentrations. Peak plasma concentrations (300-500 microM) of 5FU were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
67
1
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 28 publications
3
67
1
1
Order By: Relevance
“…At a lower pHe, in which the -ApH is large, such as occurs in solid tumours, there would be an enhancement of 5FU uptake, whereas normal cells (in which ApH is usually positive) will tend to exclude 5FU. In solid tumours this could lead to an accumulation of 5FU relative to other normal tissues, which is precisely what has been recorded in biopsies (Peters et al, 1993) and also by non-invasive '9F MRS in animal models and in the clinic (Findlay et al, 1993;Presant et al, 1994). The hypothesis suggests potential means of manipulating the tumour pH environment for therapeutic gain.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…At a lower pHe, in which the -ApH is large, such as occurs in solid tumours, there would be an enhancement of 5FU uptake, whereas normal cells (in which ApH is usually positive) will tend to exclude 5FU. In solid tumours this could lead to an accumulation of 5FU relative to other normal tissues, which is precisely what has been recorded in biopsies (Peters et al, 1993) and also by non-invasive '9F MRS in animal models and in the clinic (Findlay et al, 1993;Presant et al, 1994). The hypothesis suggests potential means of manipulating the tumour pH environment for therapeutic gain.…”
Section: Discussionmentioning
confidence: 57%
“…Enhanced retention has also been shown to be significantly associated with response Findlay et al, 1993), perhaps because higher concentrations of 5FU will sustain its anti-tumour effects by favouring the lasting presence of toxic metabolites at target tissue sites (Peters et al, 1993). The elimination half-lives (t112) of 5FU in the VX2 tumour of the rabbit , and the Walker 256 adenocarcinoma of the rat (El-Tahtawy and Wolf, 1991), were found to be about 1 h (63-73.2 and 42.2-59.4 min respectively), and greatly exceed the t 12 of 5FU in rat plasma (Au et al, 1983), which is similar to that reported in humans (5-15 min) (Cohen et al, 1982).…”
mentioning
confidence: 99%
“…10 5-FU cytotoxicity (and in consequence, clinical response) is influenced by the tissue concentration of the folate form of 5-FU, which in turn depends on the type of administration, whether oral prodrug, intravenous continuous infusion or bolus administration. 11,12 In fact, it has been postulated that the better response to the oral 5-FU prodrug 5DFUR is a consequence of the higher concentrations of intracellular 5-FU in neoplastic cells achieved after its administration. 13 To elucidate the global mechanisms of 5-FU cytotoxicity in breast cancer cells, and the molecular pathways involved in its activity, we studied gene expression profiles by microarray analysis of the well-known MCF7 breast adenocarcinoma cell line after treatment with 2 concentrations of 5-FU.…”
mentioning
confidence: 99%
“…Therefore, we measured DTD levels in a number of human normal (from colon, lung, liver, blood and head and neck) and neoplastic tissues (from colon, lung and head and neck) to determine whether, and if so in which tumour types, E09 would exert selectivity. The activity of two one-electron reductases, Cb5R and CP450R, was measured for comparison and because of their possible role in the activation of E09 under hypoxia (Plumb et al, 1994b,c;Robertson et al, 1994 (Peters et al, 1993 All the lung specimens were obtained from patients with non-small-cell lung cancer (NSCLC) undergoing radical resection. Four tumours were classified as squamous cell carcinoma (SCC), one as an adenocarcinoma (AD), one as combined adenosquamous (AS) and one as large cell (LC).…”
mentioning
confidence: 99%